Current situation and factors influencing elderly care in community day care centers: a cross-sectional study - Chen, Junyu; Zhu, Yuan; Song, Yulei; Liang, Yongqi; Wang, Lulu; Li, Weitong; Wang, Huimei; Xu, Guihua (Frontiers in Medicine, 2024)
Background The latest census data show that people over 60 years of age account for about 18.7% of the total population in China, and the aging of the population has become an irreversible trend in the 21st century. This study aimed to investigate the current status and factors influencing the care of the elderly in community day care centers in order to lay the foundation for the development of better services in community day care centers. Methods This study was a cross-sectional survey using convenience sampling in Nanjing, China. The survey instrument was the Day care and Elderly Care Service Needs Questionnaire, which included the Ability of Daily Living Assessment (ADL), the Xiao Shuiyuan Social Support Rating Scale (SSRS) and the Day care Elderly Care Service Needs Survey Form, and a general information survey. Results A total of 450 elderly people in day care centers were surveyed. The elderly had different levels of demand for day care services, especially regarding daily care. Correlation analyses indicated that age (r = 0.619), education level (r = 0.616), source of income (r = 0.582), caregiver (r = 0.557), satisfaction with care service (r = 0.603), and degree of ADL (r = 0.629) were correlated with the need for elderly day care services (all p < 0.05). The factors influencing the demand for day care services encompassed age, education level, income source, caregiver, satisfaction with service, and ADL (all p < 0.05). Conclusion Elderly care services in community day care centers are mainly based on daily and spiritual comfort, and the needs of the elderly are influenced by many factors. Timely nursing care policies and measures that target these factors are needed to improve elderly care.